ANALISIS PENGARUH ELEMEN-ELEMEN BRAND EQUITY (EKUITAS MEREK) TERHADAP KEPUTUSAN PEMBELIAN ULANG SURAT KABAR HARIAN SUARA MERDEKA DI SEMARANG - Nila Ardhianie, 12.05.51.0173; Maskur, Ali (Students Journal of Economic and Management, 2014)
Recently, the competition of the daily newspaper industry in Semarang is increasing. Old survived brands compete with new brands fought for the newspapers market in the city of Semarang . As the oldest newspaper and a market leader in Central Java, particularly in Semarang, Suara Merdeka needs to prepare a marketing strategy to survive and even better to win the competition . Data were collected through questionnaire method, with respondents of retail repeat buyer of Suara Merdeka daily newspaper in Semarang. The sampling technique used is accidental sampling technique . Data analysis used including: validity and reliability, normality test, the classic assumption test, fit model test, multiple regression analysis and hypothesis testing t test. Dependent variable is repeat purchase decision (Y) and independent varibale are brand awareness (x1 ), perceived quality (x2), brand association (x3) and brand loyalty (x4). Hypothesis testing using t-test showed that the two independent variables studied were variable brand association, and brand loyalty proved of having positive and significant effect on the dependent variable purchase decision . While the two independent variables of brand awareness and image quality but not significant positive effect on the dependent variable purchase decision. Keywords : Repeat purchase decision, brand awareness, perceived quality , brand association, brand loyalty.